An efficient waste management system with municipal solid waste incineration plant - Ozturk, Merve; Dincer, Ibrahim (WILEY PERIODICALS, INC, 2020)
This study proposes a waste management system for metropolitan cities and presents a thermodynamic analysis and emission assessment of a municipal solid waste incineration plant operating with collected wastes from the 37 municipalities of Istanbul city, Turkey. A thermodynamic analysis of the proposed system shows that 53.72 MW of electricity generation and the heat of 99.4 MW for district heating are obtained with the municipal solid waste incineration. The energy and exergy efficiencies of the plant are 55.5% and 35.4%, respectively. The rate of exergy destruction for each component in the plant and their variation with ambient temperature is calculated. The maximum rate of destruction occurs for the combustion chamber as 44.02 MW. According to the emission assessment, total CO2 emission is 45 500 ton per year and this value can be reduced to 4550 ton per year with the addition of carbon capturing and storage unit. The other released emissions from the incineration plant such as CH4, N2O, CO, NH3, and non-methane volatile organic compounds (NMVOCs) are found to be 0.15, 34.36, 201.03, 16.08, and 20.10 ton per year, respectively. (c) 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.
Keywords: efficiency; emissions; exergy; municipal solid waste; waste incineration; waste to energy; LIFE-CYCLE ASSESSMENT; TO-ENERGY; ECONOMIC-ANALYSIS; POWER-PLANTS; CAPTURE; TECHNOLOGIES; GENERATION; Energy & Fuels; Engineering; Environmental Sciences & Ecology